A single-stage AC conversion with the three-phase matrix converter for the constant V/f ratio method - Hothongkham, Prasopchok; Suathed, Sataporn; Aurairat, Anuchit (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This research introduces a single-stage direct three-phase matrix converter that utilizes the signals from the output voltage for designing pulse-width modulation signals. This converter is made up of nine bidirectional switches that use IGBT power diodes. It directly converts a steady three-phase source voltage and frequency into a variable output voltage and frequency by adjusting the frequency and modulation index of the pulse-width modulation (PWM) signals. A mathematical model is utilized to illustrate the basic principles of the matrix converter before examining its operational waveform. An evaluation is then made between the analytical waveforms and the functional waveforms, as well as the harmonics generated by the direct three-phase matrix converter. The results from both methods and processes are displayed in close agreement. Additionally, this paper discusses V/f control for induction motor drive control using this converter.